NURSING ROLE IN CHRONIC DISEASE PREVENTION AND MANAGEMENT - Salwa Sarhan Al-Shammari, Iman Qaed Mutlaq Al-Enazi, Dhoha Mohammad Daba (Chelonian Research Foundation, 2022)
Chronic diseases are a major burden on healthcare systems worldwide, and nurses play a vital role in their prevention and management. This essay explores the nursing role in chronic disease prevention and management. The methodology involves a review of relevant literature on the topic, with a focus on the role of nurses in promoting healthy behaviors, educating patients, and coordinating care for individuals with chronic conditions. The results highlight the importance of nursing interventions in improving health outcomes and quality of life for individuals with chronic diseases. The discussion emphasizes the need for collaboration among healthcare providers and the integration of evidence-based practices to optimize patient care. In conclusion, nurses have the knowledge and skills to address the complex needs of patients with chronic diseases, making them invaluable members of the healthcare team.